Quality of compounded hydrocortisone capsules used in the treatment of children. Issue 2 (August 2017) - Neumann, Uta; Burau, Daniela; Spielmann, Sarah; Whitaker, Martin J; Ross, Richard J; Kloft, Charlotte; Blankenstein, Oliver
Abstract : Objectives: Due to the lack of paediatric-licensed formulations, children are often treated with individualized pharmacy-compounded adult medication. An international web-based survey about the types of medication in children with adrenal insufficiency (AI) revealed that the majority of paediatric physicians are using pharmacy-compounded medication to treat children with AI. Observations of loss of therapy control in children with congenital adrenal hyperplasia with compounded hydrocortisone capsules and regained control after prescribing a new hydrocortisone batch led to this 'real world' evaluation of pharmacy-compounded paediatric hydrocortisone capsules. Methods: Capsule samples were collected randomly from volunteering parents of treated children suffering from congenital adrenal hyperplasia from all over Germany. Analysis of net mass and hydrocortisone content by high-performance liquid chromatography with ultraviolet (HPLC-UV) detection method was performed based on the European Pharmacopeia. Results: In a total of 61 batches that were sent, 5 batches could not be analysed because of missing dose information, insufficient number of capsules or were not possible to be evaluated. Fifty-six batches containing 1125 capsules were evaluated. 21.4% of the batches revealed insufficiency in uniformity of net mass or drug content and additional 3.6% failed because they did not contain the labelled drug. Conclusions: Compounded medication is a possible cause of variation of steroid doses in children with adrenal insufficiency or congenital adrenal hyperplasia, putting these vulnerable patients at risk of poor disease control and adrenal crisis. These data may apply to other individualized compounded oral medication as well, emphasizing the need for development of licensed paediatric formulations approved by regulatory authorities.